Correlation between Family Support and Compliance with Dietary Control in Diabetes Mellitus - Faswita, Wirda (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
Diabetes Mellitus (DM) characterized by an increase in blood glucose levels caused due to chronic metabolic disorders characterized by deficiencies in the production and utilization of the hormone insulin. Family has an influence on the attitude and acceptance of health education for people with Diabetes Mellitus. Family support is needed to improve dietary compliance in people with Diabetes Mellitus. The purpose of this study is to determine the relationship between family support and dietary control compliance in people with Diabetes Mellitus in the Binjai City Health Center work area in 2023. This type of research is quantitative with a correlation design carried out in the working area of the Binjai City Health Center in March-July 2023. The population in this study was all Diabetes Mellitus sufferers in the working area of the Binjai City Health Center which amounted to 155 respondents. The samples in this study were taken using purposive sampling techniques as many as 30 respondents . The results of family support research in people with Diabetes Mellitus the majority of respondents had family support in a good category as many as 15 respondents (50%). Meanwhile, dietary compliance shows that the majority of respondents have compliance as many as 19 respondents (63.3%). Based on the results of the chi-squertes test above, we get a p value of 0.000 (p < 0.005) which means that there is a relationship between family support and dietary control compliance in patients with Diabetes Mellitus Ho rejected Ha accepted. It is expected that health workers can provide health education to families in handling diet control in patients with Diabetes Mellitus.